2015
DOI: 10.1088/0004-637x/805/2/185
|View full text |Cite
|
Sign up to set email alerts
|

An Ammonia Spectral Map of the L1495-B218 Filaments in the Taurus Molecular Cloud. I. Physical Properties of Filaments and Dense Cores

Abstract: We present deep NH 3 observations of the L1495-B218 filaments in the Taurus molecular cloud covering over a 3 degree angular range using the K-band focal plane array on the 100m Green Bank Telescope. The L1495-B218 filaments form an interconnected, nearby, large complex extending over 8 pc. We observed NH 3 (1,1) and (2,2) with a spectral resolution of 0.038 km/s and a spatial resolution of 31 . Most of the ammonia peaks coincide with intensity peaks in dust continuum maps at 350 µm and 500 µm. We deduced phys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
101
3
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(120 citation statements)
references
References 90 publications
(138 reference statements)
15
101
3
1
Order By: Relevance
“…The regions observed by Seo et al (2015) which were also observed as part of the JCMT GBS are those identified as B7, B10 and B211 on Figure 4.14. It can be seen that the NH 3 and 850-µm continuum emission appear to be tracing the same material -the dense cores within the filament (c.f.…”
Section: Internal Energymentioning
confidence: 92%
See 4 more Smart Citations
“…The regions observed by Seo et al (2015) which were also observed as part of the JCMT GBS are those identified as B7, B10 and B211 on Figure 4.14. It can be seen that the NH 3 and 850-µm continuum emission appear to be tracing the same material -the dense cores within the filament (c.f.…”
Section: Internal Energymentioning
confidence: 92%
“…We determine the internal energy of our cores using the linewidths determined for cores in L1495 in ammonia (NH 3 ) by Seo et al (2015). Seo et al (2015) observed the NH 3 (1,1) -rest frequency 23.694 GHz -and (2,2) -rest frequency 23.723 GHz -transitions using the 100-m Robert C. Byrd Green Bank Telescope, with a beam size of 31 arcsec and a velocity resolution of 3.05 kHz.…”
Section: Internal Energymentioning
confidence: 99%
See 3 more Smart Citations